Faire théorie pour faire science ? - Lucile Dumont (Revue d’Histoire des Sciences Humaines)
The paper questions how theoretical production has been conceived as a way to scientize French literary studies in the 1960s and 1970s. The emergence of structural methods engaged reflections on scientificity in the Humanities, which were extended in the semiology developed around Roland Barthes. The question of science then appeared through the debates on the role of literary criticism. The end of the 1960s is marked by an evolution towards an aesthetic and theoretical radicalness which identified theory and science. Eventually, the collective construction of poetics around Genette and Todorov shows at the same time how theory is prioritized over the question of science, and the complex relationship with literature in the definition of a science of literature. The paper relies on a study of some theoretical texts and of several theorists’ trajectories, in a perspective of historical sociology of Social Sciences and Humanities.